1993
DOI: 10.1055/s-2007-1014349
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Activity in Serum of Neuroleptic-Naive Psychiatric Inpatients

Abstract: It was not possible to replicate the finding of increased PLA2 activity in schizophrenic patients in our sample of patients never treated with neuroleptics before.(ABSTRACT TRUNCATED AT 250 WORDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 9 publications
0
11
0
3
Order By: Relevance
“…64,72,80,81 Analysis of post-mortem brain tissue found calcium-dependent PLA2 activity was decreased, rather than increased. 78 Could response to antipsychotic medication be due to interactions with PLA2s?…”
Section: Calcium-dependent Pla2mentioning
confidence: 99%
See 1 more Smart Citation
“…64,72,80,81 Analysis of post-mortem brain tissue found calcium-dependent PLA2 activity was decreased, rather than increased. 78 Could response to antipsychotic medication be due to interactions with PLA2s?…”
Section: Calcium-dependent Pla2mentioning
confidence: 99%
“…64,72,80 A small population of drug naïve patients had normal calcium-dependent PLA2 activity. 81 Niacin insensitivity and PLA2 activity The increased calcium-independent PLA2 activity associated with schizophrenia is greater still in the niacin insensitive sub group. 62 As reported, 8 weeks of medication reduced the abnormally high calciumindependent PLA2 activity.…”
Section: Calcium-dependent Pla2mentioning
confidence: 99%
“…Ross, Hudson, Erlich, Warsh, and Kish (1997) demonstrated that contradictory findings in previous reports (Hudson, Gotowiec, Seeman, Warsh, & Ross, 1999;Ross et al, 1997;Gattaz et al, 1995;Albers, Meurer, Marki, & Klotz, 1993;Noponen et al, 1993;Gattaz et al, 1990;Gattaz, Kollisch, Thuren, Virtanen, & Kinnunen, 1987) could be explained by different PLA2 assays used (the negative studies used an assay based on bacterial antibodies). In keeping with reductions of membrane AA in schizophrenia, an increased calcium-independent PLA2 activity has also been demonstrated in post mortem brain tissue of the temporal cortex of patients with schizophrenia (Ross, Turenne, Moszczynska, Warsh, & Kish, 1999).…”
Section: Phospholipases A2 Key-metabolizing Enzymes Of Bioactive Lipidsmentioning
confidence: 96%
“…Noponen et al 16 confirmaram o aumento da atividade da PLA2 plasmática em esquizofrenia; entretanto neste estudo, o aumento foi também indicado em outros pacientes psiquiátricos não-esquizofrênicos, questionando assim a especificidade de nosso achado para a esquizofrenia. Albers et al 17 não encontraram diferença na atividade da enzima no plasma de esquizofrênicos comparados com controles. Como a PLA2 no plasma representa um grupo heterogêneo de enzimas, sugerimos que nos 3 laboratórios (Gattaz, Noponen e Albers), com o uso de méto-dos laboratoriais diferentes, detectou-se a atividade de diferentes formas moleculares da enzima, o que explicaria a aparente inconsistência dos achados.…”
unclassified